Neurotoxicity of Tris (1, 3-dichloroisopropyl) phosphate in Caenorhabditis elegans. (30th May 2022) - Tang, Jielin; Li, Jiayi; Zhou, Qinyu; Kuerban, Guzailinuer; Qin, Jinyan; Zhang, Hongdan; Sun, Rongli; Yin, Lihong; Pu, Yuepu; Zhang, Juan
Abstract: As a new type of flame retardant, Organic Phosphate Flame Retardant has been widely used worldwide. The purpose of our research is to determine the neurotoxicity of Tris (1, 3-dichloroisopropyl) phosphate (TDCPP) to Caenorhabditis elegans and its mechanism. L1 larvae wild-type C. elegans were exposed to different concentrations of TDCPP, and the effects on motor behavior (head thrashes, body bends, pumping times, chemotaxis index), ROS levels, and p38MAPK signaling pathway-related gene expression levels were measured. Three transgenic nematode strains, BZ555, DA1240, and EG1285, were also used to study the effects of TDCPP on nematode dopamine neurons, glutamate neurons, and GABA neurons. The results showed that TDCPP can inhibit the head thrashes and body bends of the nematode, reduce dopamine production, increase the level of ROS in the body, and affect the expression of genes related to the p38MAPK signaling pathway. We next employed ROS production and motor behavior as toxicity assessment endpoints to determine the involvement of p38 MAPK signaling in the regulation of response to TDCPP. The results showed that the nematodes with low expression of pmk-1 were less sensitive to the TDCPP. It was suggested that TDCPP had neurotoxicity and regulated neurotoxicity to C. elegans by activating the p38-MAPK signaling pathway. The research in this article provides important information for revealing the environmental health risks of organophosphorus flame retardants and their toxic mechanism of action.